Do stockholders appreciate CSR? The role of firm visibility, financial slack, and monitoring - Uyar, Ali; Lakhal, Faten; Kuzey, Cemil; Karaman, Abdullah (Management international / International Management / Gestiòn Internacional, 2024)
Although numerous past studies have examined the association between corporate social responsibility (CSR) and firm value, the findings have been inconsistent. This study examines how firm visibility, financial slack, and monitoring affected the relationship between CSR and firm value. We find that CSR performance and its three dimensions, that is, environmental, social, and governance—have positive effects on firm value. The results also show that under slack resources and strong corporate governance, the positive effect of CSR on firm value is strongly supported. These results suggest that managers should be aware that they can also attract shareholders’ interests in the stock market while addressing stakeholders’ concerns, especially when the firm has available financial slack and strong board monitoring.